Psychometric properties of the assessment of COVID‐19 attitudes and behaviors. Issue 1 (5th January 2021) - Silverstein, Madison W.; Mekawi, Yara; Alonzi, Sarah P.; La Torre, Adelaide
Abstract: Developing psychometrically validated assessment tools to examine social and intergroup processes related to COVID‐19 is fundamental for creating interventions that reduce the spread of this virus. Thus, this manuscript aimed to evaluate the psychometric properties of a new measure, Assessment of COVID‐19 Attitudes and Behaviors (ACAB), that assesses COVID‐19‐related attitudes (e.g., about physical distancing, xenophobia), behaviors (e.g., helping others versus prioritizing own needs), and beliefs (e.g., about others' roles in spreading COVID‐19). We used exploratory and confirmatory factor analyses (EFA, CFA) to provide factor analytic support and Fisher's r ‐to‐ z transformation to provide construct validity evidence. EFA revealed and CFA confirmed a four‐factor structure of social distancing adjustment, self‐prioritization, prosocial behaviors, and belief in conspiracies. Fisher's r ‐to‐ z transformation provided evidence for the construct validity of the four factors. This psychometrically validated instrument will enhance social science researchers' ability to accurately identify and explicate psychological processes related to COVID‐19.